2005
DOI: 10.1111/j.1742-4658.2005.04593.x
|View full text |Cite
|
Sign up to set email alerts
|

An engineered disulfide bridge mimics the effect of calcium to protect neutral protease against local unfolding

Abstract: The extreme thermal stabilization achieved by the introduction of a disulfide bond (G8C/N60C) into the cysteine-free wild-type-like mutant (pWT) of the neutral protease from Bacillus stearothermophilus[Mansfeld J, Vriend G, Dijkstra BW, Veltman OR, Van den Burg B, Venema G, Ulbrich-Hofmann R & Eijsink VG (1997) J Biol Chem272, 11152-11156] was attributed to the fixation of the loop region 56-69. In this study, the role of calcium ions in the guanidine hydrochloride (GdnHCl)-induced unfolding and autoproteolysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 44 publications
2
21
0
Order By: Relevance
“…The formation of the disulfide bond Cys52‐Cys65 was helpful for the WF146 protease to resist autolysis, probably by decreasing the flexibility of the autolysis loop (positions 64–70). Similar proposal has also been suggested for a thermolysin‐like protease from Bacillus stearothermophilus , where the introduction of a disulfide bond into the enzyme enhanced the enzyme stability toward autolysis due to increased rigidity of local region rather than stabilization of the enzyme toward global unfolding [32,33]. In addition, it has been reported that the thermostable thermitase possessed three stabilizing Ca 2+ binding sites, of which the second one lay in the loop of residues 59 to 65 (thermitase numbering) and reduced the local mobility of the accessible loop (Fig.…”
Section: Resultssupporting
confidence: 68%
“…The formation of the disulfide bond Cys52‐Cys65 was helpful for the WF146 protease to resist autolysis, probably by decreasing the flexibility of the autolysis loop (positions 64–70). Similar proposal has also been suggested for a thermolysin‐like protease from Bacillus stearothermophilus , where the introduction of a disulfide bond into the enzyme enhanced the enzyme stability toward autolysis due to increased rigidity of local region rather than stabilization of the enzyme toward global unfolding [32,33]. In addition, it has been reported that the thermostable thermitase possessed three stabilizing Ca 2+ binding sites, of which the second one lay in the loop of residues 59 to 65 (thermitase numbering) and reduced the local mobility of the accessible loop (Fig.…”
Section: Resultssupporting
confidence: 68%
“…40 Anchoring a loop in a neutral protease from Bacillus stearothermophilus, whose local unfolding is responsible for formation of an intermediate, to the rest of protein by a disulfide bridge prevented formation of the intermediate. 41 Stabilization of a loop in cytochrome c, whose local unfolding causes formation of intermediate and aggregation in the presence of benzyl alcohol, caused reduction in aggregation. 42 Recently, roles of native protein structure and amino acid sequence in aggregation were also highlighted.…”
Section: Discussionmentioning
confidence: 99%
“…Using a variety of stabilization strategies, highly stable variants of TLP‐ste could be engineered 14, 56. One particularly successful example was the introduction of a designed disulfide bridge (through mutations G8C & N60C) that covalently linked the N‐terminal β‐strand to one of the other strands in the N‐terminal three‐strand β‐sheet 28, 58. Other mutations in the region were also successful for stabilization of TLP‐ste (e.g.…”
Section: The 5 Steps In the Life Of Tlp‐stementioning
confidence: 99%